The effect of coarse aggregate on fresh and hardened properties of self-compacting concrete (SCC) - Khaleel, O.R.; Al-Mishhadani, S.A.; Abdul Razak, H. (2011)
Self Compacting Concrete (SCC) is new type of concrete that posse's property of high flow ability, passing ability and stability. To achieve SCC, many factors must be investigated. Coarse aggregate is one of these factors that have a significant influence on SCC. This paper presents the coarse aggregate properties such as maximum size, texture and type of coarse aggregate that have a direct effect on achieving SCC. Three types of coarse aggregate are used, namely crush gravel, uncrushed gravel and crush limestone. To determine the workability, different test methods are adopted such as slump flow, V-funnel, L-box and U-box test. It was found that by increasing the maximum size of coarse aggregate, flowability and passing ability reduced. In addition it was observed that when uncrushed gravel was used in the concrete mixture, flow ability, passing ability and segregation resistance increased as compared to concrete with crushed gravel. Furthermore, the inclusion of 10 HRM as a partial replacement by weight of cement leads to reduce flow ability and increase viscosity. The compressive and flexural strengths and modulus of elasticity was measured. It was noticed that concrete mixes prepared with crushed limestone showed higher strengths and modulus of elasticity than concrete mixes prepared with crushed and uncrushed gravel. In addition, lower maximum size of coarse aggregate leads to higher strengths compared to higher maximum size of coarse aggregate in SCC mixes.